Clinical Outcomes of Virologically-Suppressed Patients with Pre-existing HIV-1 Drug Resistance Mutations Switching to Rilpivirine/Emtricitabine/Tenofovir Disoproxil Fumarate in the SPIRIT Study*. Issue 1 (2nd January 2016) - Porter, Danielle P.; Toma, Jonathan; Tan, Yuping; Solberg, Owen; Cai, Suqin; Kulkarni, Rima; Andreatta, Kristen; Lie, Yolanda; Chuck, Susan K.; Palella, Frank; Miller, Michael D.; White, Kirsten L.
Abstract : Objectives : Antiretroviral regimen switching may be considered for HIV-1-infected, virologically-suppressed patients to enable treatment simplification or improve tolerability, but should be guided by knowledge of pre-existing drug resistance. The current study examined the impact of pre-existing drug resistance mutations on virologic outcomes among virologically-suppressed patients switching to Rilpivirine (RPV)/emtricitabine (FTC)/tenofovir disoproxil fumarate (TDF). Methods : SPIRIT was a phase 3b study evaluating the safety and efficacy of switching to RPV/FTC/TDF in virologically-suppressed HIV-1-infected patients. Pre-existing drug resistance at baseline was determined by proviral DNA genotyping for 51 RPV/FTC/TDF-treated patients with known mutations by historical RNA genotype and matched controls and compared with clinical outcome at Week 48. Results : Drug resistance mutations in protease or reverse transcriptase were detected in 62.7% of patients by historical RNA genotype and in 68.6% by proviral DNA genotyping at baseline. Proviral DNA sequencing detected 89% of occurrences of NRTI and NNRTI resistance-associated mutations reported by historical genotype. Mutations potentially affecting RPV activity, including E138A/G/K/Q, Y181C, and H221Y, were detected in isolates from 11 patients by one or both assays. None of the patients with single mutants had virologic failure through Week 48. One patient with pre-existing Y181Y/C and M184I by proviral DNA genotyping experienced virologic failure. Nineteen patients with K103N present by historical genotype were confirmed by proviral DNA sequencing and 18/19 remained virologically-suppressed. Discussion : Virologic success rates were high among virologically-suppressed patients with pre-existing NRTI and NNRTI resistance-associated mutations who switched to RPV/FTC/TDF in the SPIRIT study. While plasma RNA genotyping remains preferred, proviral DNA genotyping may provide additional value in virologically-suppressed patients for whom historical resistance data are unavailable.